2005
DOI: 10.1111/j.1399-0004.2005.00519.x
|View full text |Cite
|
Sign up to set email alerts
|

Attenuated familial adenomatous polyposis and Muir–Torre syndrome linked to compound biallelic constitutional MYH gene mutations

Abstract: Attenuated familial adenomatous polyposis and Muir-Torre syndrome linked to compound biallelic constitutional MYH gene mutations.Peculiar dermatologic manifestations are present in several heritable gastrointestinal disorders. Muir-Torre syndrome (MTS) is a genodermatosis whose peculiar feature is the presence of sebaceous gland tumors associated with visceral malignancies. We describe one patient in whom multiple sebaceous gland tumors were associated with early onset colon and thyroid cancers and attenuated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(51 citation statements)
references
References 31 publications
2
47
0
2
Order By: Relevance
“…12,16 Thyroid cancer occurred in 2 patients 31 (own study), the histology was different (papillary and follicular carcinoma, respectively). Recently, 2 affected siblings with multiple pilomatricomas 32 and a patient with multiple seba- ceous adenomas on the forehead and neck 31 were described, indicating some kind of phenotype variability. In another study, breast cancer has been diagnosed in 4 (18%) of 22 female MAP patients (age at diagnosis of breast cancer 49-76 years).…”
Section: Frequency and Phenotype Of Mapmentioning
confidence: 99%
“…12,16 Thyroid cancer occurred in 2 patients 31 (own study), the histology was different (papillary and follicular carcinoma, respectively). Recently, 2 affected siblings with multiple pilomatricomas 32 and a patient with multiple seba- ceous adenomas on the forehead and neck 31 were described, indicating some kind of phenotype variability. In another study, breast cancer has been diagnosed in 4 (18%) of 22 female MAP patients (age at diagnosis of breast cancer 49-76 years).…”
Section: Frequency and Phenotype Of Mapmentioning
confidence: 99%
“…A recent report describes the presence of sebaceous gland tumors in several individuals positive for germline MYH mutations. 20 Our analysis indicated that neither the proband nor his clinically affected family members carried the common germline MYH mutations. Furthermore, given the segregation of a complex germline MSH2 mutation in this family and the presence of a subset of MSI-H tumors, it is not likely that their colorectal tumors belong to the MMRproficient Muir-Torre category.…”
Section: Discussionmentioning
confidence: 75%
“…The base excision repair gene MYH has been proposed to be a likely candidate gene that is mutated in these families. 19,20 Biallelic inactivation of MYH can lead to an autosomal recessive form of inherited colorectal cancer known as MYH associate polyposis. A recent report describes the presence of sebaceous gland tumors in several individuals positive for germline MYH mutations.…”
Section: Discussionmentioning
confidence: 99%
“…Tip 1 MTS'de malignite erken yaşta başlar ve ailede güçlü kanser öyküsü vardır. Hastaların %31'ini oluşturan tip 2 MTS'de ise baz eksizyon tamir geni olan MuY (MYH) mutasyonu saptanmıştır 7 . Malignite geç başlangıçlıdır ve aile hikayesi yoktur.…”
Section: Olgu Sunumuunclassified